Analisis Ekstrak Etanol Buah Labu Kuning (Cucurbita Moschata D.) - Nur Hasanah; Dede Rival Novian (Parapemikir : Jurnal Ilmiah Farmasi, 2020)
The ethanol extract of yellow pumpkin fruit (Cucurbita Moschata D.) has been recognized to have flavonoid compounds using the colorimetric method (AlCl3). The purpose of this study was to determine the levels of flavonoids in the ethanol extract of yellow pumpkin fruit (Cucurbita Moschata D.). Ethanol extract of pumpkin fruit (Cucurbita Moschata D.) was obtained by maceration using 70% ethanol with a concentration of 5 ppm. The concentration of flavonoid compounds in yellow pumpkin fruit extract (Cucurbita Moschata D.) was carried out using a UV-Visible spectrophotometer with a comparative material namely quercetin using the colorimetric method (AlCl3). The measurement of the quercetin calibration curve used a concentration of 2,4,6,8,10 ppm, and the equation y = 0.18x + 0.2785 with the correlation coefficient (r) = 0.9877. The measurement of maximum wavelength absorption is carried out in the range of 200-600 nm. The maximum wavelength produced is 268 nm at a concentration of 2 ppm or 2 πg / mL. The absorbance value of the sample of ethanol extract of pumpkin fruit is 0,2875; 0,2894; 0,2976 with an average of 0,2915. Based on the results of the research that has been done, it can be concluded that the ethanol extract of yellow pumpkin fruit (Cucurbita Moschata D.) has a level of flavonoid compounds 0,00288 mg/g or 0,288% at concentration of 5 ppm. Keyword – level, Flavonoid, UV-Vis, Cucurbita moschata, Pumpkin